The Psychological Pollution (Journal of the College of Education for Women, 2019)
The psychological pollution term comes from the realism that we live in its world. Thisrealism threatens our privet and the identity of our civilization. There is complete believe thatthe literature of psychological pollution is insufficient to cover the whole horizons of thisterm.The psychological pollution has its root in the theories of the development of humanitieswithin the organization of the history. Some of these theories are the exceptional culturaltheory, the faithfulness theory and the integration theory and the identity losing.The psychological pollution handles several concepts such as the engagement, the socialdecay and the concept of cultural invasion.